МУИС-ийн утга зохиол судлал хөтөлбөрийн бакалаврын судалгааны ажлын чиглэлийг тодорхойлох нь : To define the research tendency of bachelor diploma in the literature curricula in National University of Mongolia (2016-2016)) - Г., Нарантунгалаг (Mongolian Studies, 2023)
A study of contemporary literature and folklore is mainly studied by students of undergraduate literature program. However, a number of bachelor diploma on journalism has increased well in recent years. As a result of a course of primary source study is not included in the curricula, students are could not attend in class of the ancient literature.